2017
DOI: 10.1016/j.jtcme.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of Achillea wilhelmsii on the isolated rat heart in ischemia–reperfusion

Abstract: ContextThere are some reports about protective effects of Achillea on the heart.ObjectiveWe investigated the effect of Achillea wilhelmsii extract on cardiac function during ischemia–reperfusion (I/R) injury in the isolated rat heart.Materials and methods60 male Wistar rats were randomly divided into 6 groups; 1: Control group, 2: Control-ischemia (CI) 3: vitamin C (10 mg/kg), 4–6: Extract groups (E 100, E 200 and E 400 mg/kg). The animals received normal saline, vitamin C or A. wilhelmsii extract orally for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…Due to the effect of "Achillea millefolium" extract on increasing levels of antioxidant enzymes in the heart muscle, Mahmoudabadi et al have reported a positive effect of this extract on antioxidant enzymes level in rat model of heart ischemia-reperfusion [69] The results of our experiments also have showed the beneficial effect of this plant against the side effects of cisplatin.…”
Section: Discussionsupporting
confidence: 71%
“…Due to the effect of "Achillea millefolium" extract on increasing levels of antioxidant enzymes in the heart muscle, Mahmoudabadi et al have reported a positive effect of this extract on antioxidant enzymes level in rat model of heart ischemia-reperfusion [69] The results of our experiments also have showed the beneficial effect of this plant against the side effects of cisplatin.…”
Section: Discussionsupporting
confidence: 71%
“…A. wilhelmsii is able to decrease the activity of lactate dehydrogenase (LDH), creatine kinase (CK) and malondialdehyde (MDA) levels, and to increase the superoxide dismutase (SOD) and catalase (CAT) activities. In summary, it was able to improve the myocardial oxidative stress states on cardiac function during ischemia/reperfusion injury in rat (15). A. phrygia ethyl acetate extracts also showed a remarkable enzyme inhibitory potential (16), and the hydroalcoholic extract of A. millefolium demonstrated in vivo antidiabetic effects, through inhibition of α-glucosidases, insulin secretion and insulin secretagogue activities (17).…”
Section: Introductionmentioning
confidence: 93%
“…This plant holds a remarkable place in traditional Persian medicine, with a particular indication for the treatment of pulmonary affections, and it is used by the local population for a variety of ailments [4]. Recent investigations have substantiated these traditional uses with a scientific approach and activity on irritable bowel syndrome and ulcerative colitis [5,6], and improvement of oxidative stress-related myocardial injury [7] have been demonstrated. Asgary et al [8] have reported a significant activity of A. wilhelmsii extracts in inducing a decrease in triglycerides and LDL-cholesterol levels after 2-4 months of the administration, a result supported by Khazneh et al [9] in a more recent investigation.…”
Section: Introductionmentioning
confidence: 99%